A literature review: Bacterial resistance (International Seven Journal of Health Research, 2023)
The discovery and use of antibiotics was a major step forward for global public health. Since then, it has been possible to treat several types of infection with this class of drugs. For a long time, it was done in a disorderly way, which caused the most resistant bacteria to emerge. This work addresses how these microorganisms acquire this resistance, and the consequences. The present study aimed to analyze, through a literature review, about bacterial resistance, thus also showing the consequences and solutions to alleviate the situation. To this end, a bibliographic review of articles and books was carried out on several websites, available in the Google Scholar electronic library, Scielo. This is a topic that deserves attention today.